On the limit theorems of large deviation for sums of random discrete variables - Vaitkus, P. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Вайткус. О локальных предельных теоремах для больших уклонений сумм независимых случайных дискретных величин P. Vaitkus. Apie nepriklausomų atsitiktinių diskretinių dydžių sumų didžiųjų nukrypimų ribines lokalines teoremas